COVID-19 Pandemic’s Impact on Company Activities in Romania - Corina - Ionela DUMITRESCU; Natalia MANEA; Răzvan – Marian MARINESCU; Nicoleta NICULESCU; Răzvan – Mihai DOBRESCU; Roxana – Adriana PUIU (Communications of International Proceedings, 2021)
This paper aims at analyzing the way of action of the Romanian entrepreneurs in the context of the COVID 19 pandemic, their reactions and ways of adapting to the current market. The research is a qualitative one conducted on a group of 10 entrepreneurs. The technique used is the in-depth interview and the tool used is the interview guide. The research concludes that Romanian entrepreneurs have been helped by both creativity, resilience and flexibility to the market requirements and their employees and customers as well.
Keywords: entrepreneurs; COVID 19; qualitative research; Romania.